Re-evaluation ofAfro-postmodernism in Chinua Achebe’s and Ben Okri’s trilogy novels: An approach to postcolonial and magical realist literature - Pegu, Dermee (International Journal of Psychosocial Rehabilitation, 2020)
Trilogy is a series of three books, plays, etc. written by the same person and together forming an extended, unified work written about the same situation or characters, forming a continuous story. The paper attempts to explore the elements of post modernism, postcolonial and magical realism in Chinua Achebe’s The African Trilogy, the book series that comprised of three books i.e. Things Fall Apart, No Longer at Ease, Arrow of God and Ben Okri's trilogy: The Famished Road, Songs of Enchantment, Infinite Riches. It will review the origin of its traditional literary works and the major readings of the trilogy novels in the light of the concepts associated with oral tradition, belief, realism and culture marked by the overall indeterminacy that captures a society caught between its traditional roots and the demands of a rapidly changing world.The paper will highlight the genres that make up the trilogy novels in its complex and extreme intertextuality, that would alternatively put forward the elements of Afro-postmodernism, Afro-coloniality and the African American narrative strategy.Hence, it will explore the evolution of African writers, rise of African novels consisting of constructive narrative strategy revealing traditional and cultural forms and its relevance with the Postmodern African Literature.